2011
DOI: 10.1159/000327535
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Serum Tryptase in a General Population: The Relationship of Serum Tryptase to Obesity and Asthma

Abstract: Background: Recent studies indicate that mast cells are more abundant in the obese state. Total serum tryptase (ST) is a marker of mast cell numbers or activity. Since obesity and asthma have been consistently linked in epidemiological studies, a possible higher mast cell activity in obesity could be a factor between the two conditions. The aim of this study was to investigate determinants of ST and whether a potential association between obesity and allergic respiratory disease would be influenced by levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
43
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 67 publications
4
43
1
1
Order By: Relevance
“…Fenger etal. [21] also showed that serum tryptase, a marker of mast cell number and activity, increased with increasing BMI. It is plausible that the relationship between BMI and response to histamine is mediated by increased mast cell activity or count.…”
Section: Discussionmentioning
confidence: 87%
“…Fenger etal. [21] also showed that serum tryptase, a marker of mast cell number and activity, increased with increasing BMI. It is plausible that the relationship between BMI and response to histamine is mediated by increased mast cell activity or count.…”
Section: Discussionmentioning
confidence: 87%
“…However, serum tryptase seems not to be associated with atopy and allergic respiratory disease [29], and patients with indolent mastocytosis without skin lesions have been found to have a high reaction rate to insect stings but a lower baseline serum tryptase than other groups of mastocytosis patients [30]. …”
Section: Discussionmentioning
confidence: 99%
“…However, tryptase was significantly increased only in obese children, compared to non-obese children and not across all age groups. This may be explained by the effect of age on tryptase, as tryptase levels increase in adults independent of BMI [22], which may have confounded our analysis. In another human study, WARD et al [23] also found no association between BMI and tryptase in obese and non-obese children with and without glucose intolerance and diabetes mellitus ( p=0.068).…”
Section: Discussionmentioning
confidence: 99%